Who needs to be screened for primary aldosteronism? - Wei-Chieh Huang; Feng-Hsuan Liu; Hao-Min Cheng; Yi-Chun Tsai; Yen-Ta Huang; Tai-Shuan Lai; Yen-Hung Lin; Vin-Cent Wu; Hsien-Li Kao; Charles Jia-Yin Hou; Kwan-Dun Wu; Szu-Tah Chen; et al. (Journal of the Formosan Medical Association, 2024)
The prevalence of patients with primary aldosteronism (PA) is about 5%–15% in hypertensive patients, and it is common cause of secondary hypertension in clinical practice. Two major causes of PA are noted, namely bilateral adrenal hyperplasia and aldosterone-producing adenoma, and the general diagnosis is based on three steps: (1) screening, (2) confirmatory testing, and (3) subtype differentiation (Figure 1). The recommendation for screening patients is at an increased risk of PA, here we focus on which patients should be screened for PA, not only according to well-established guidelines but for potential patients with PA. We recommend screening for 1) patients with resistant or persistent hypertension, 2) hypertensive patients with hypokalemia (spontaneous or drug-induced), 3) young hypertensive patients (age <40 years), and 4) all hypertensive patients with a history of PA in first-degree relatives. Moreover, we suggest screening for 1) hypertensive patients themselves or first-degree relatives with early target organ damage, such as stroke and other diseases, 2) all hypertensive patients with a concurrent adrenal incidentaloma, 3) hypertensive patients with obstructive sleep apnea, 4) hypertensive patients with atrial fibrillation unexplained by structural heart defects and/or other conditions resulting in the arrhythmia, 5) hypertensive patients with anxiety and other psychosomatic symptoms, and 6) hypertensive patients without other comorbidities to maintain cost-effectiveness.